A Retrospective Analysis Assessing Paravalvular Leak and Pacemaker Implantation Using TEE and Non‐Contrast CT for CKD Patients Compared With CT Angiography for Annular Sizing Pre‐TAVR - Michael O'Shaughnessy; Roxana Tabrizi; Derek Pham; Nicholas Jackson; Olcay Aksoy; Andre Akhondi; Jeanne Huchting; Richard Shemin; Murray Kwon; Peyman Benharash; Brandon Kim; Amir Rabbani (Health Science Reports)
ABSTRACT Background and Aims Transcatheter aortic valve replacement (TAVR) has become the treatment of choice for many patients with severe aortic stenosis. Proper pre‐procedure sizing of the aortic annulus is crucial in preventing post‐TAVR complications. This is typically performed with CT angiography, but the use of contrast is controversial in patients with chronic kidney disease (CKD). Methods This study of 557 patients from 2016 to 2021 sought to evaluate a contrast‐sparing protocol for balloon expandable TAVR evaluation in patients with CKD, in which patients with glomerular filtration rate of less than 40 would undergo transesophageal echocardiogram (TEE) and CT without contrast (83 patients) for aortic annular sizing instead of CT angiography (445 patients). Results We found that there was no significant difference in rates of greater than trace or greater than mild paravalvular leak between the two groups at hospital discharge, 30 days, or 1‐year post‐TAVR. We also found no difference in rates of permanent pacemaker implantation at these same time points. Conclusions This suggests that TEE and non‐contrast CT could be a viable alternative to CTA in patients with CKD, although more research into other variables such as mortality and other post‐procedural complications is necessary.